Commonalities of Atomic Layer Deposition of Oxide Coatings on Activated Carbons for 3.5 V Electric Double Layer Supercapacitors - Tan, Daniel Q.; Song, Guanghui; Gandla, Dayakar; Zhang, Fuming (Frontiers in Energy Research, 2020)
High voltage electric double layer capacitors with reliable cycling performance are in high demand for energy storage applications. In this research, studies of the process-structure-property relations of commercial activated carbon electrode modified with atomic layer deposition (ALD) have been performed in terms of coating of various oxide compounds. These investigations have yielded similar enhancements of cycling performance at high voltages (3.5 V) enabled by the ALD coating of oxides on activated carbon surfaces. The commonalities are the phenomenal increase in capacitance retention of coin cell supercapacitors after 1,000 charge/discharge cycles regardless of the electric nature of ALD deposited oxides. Minor differences in coating morphologies and uniformities were observed between the aluminum oxide, titanium oxide, and manganese-cobalt oxide. ALD coating of these oxides of about 20-growth cycle (1–2 nm in thickness) was found to effectively result in reliable cycling performance, lower impedance, and significantly low leakage current. The authors proposed a modified Gouy-Chapman-Stern model to explain the remarkable increase in operating voltage and cycling performance by the increased Stern layer thickness due to the ALD oxide coating. These results demonstrate that the ALD oxide coating has excellent potential for activated carbons for high operating voltage and energy density supercapacitor.